Halogencarbene-free Ciamician-Dennstedt single-atom skeletal editing - Shaopeng Liu; Yong Yang; Qingmin Song; Zhaohong Liu; Paramasivam Sivaguru; Yifan Zhang; Graham de Ruiter; Edward A. Anderson; Xihe Bi (Nature Communications)
Abstract Single-atom skeletal editing is an increasingly powerful tool for scaffold hopping-based drug discovery. However, the insertion of a functionalized carbon atom into heteroarenes remains rare, especially when performed in complex chemical settings. Despite more than a century of research, Ciamician-Dennstedt (C-D) rearrangement remains limited to halocarbene precursors. Herein, we report a general methodology for the Ciamician-Dennstedt reaction using α-halogen-free carbenes generated in situ from N-triftosylhydrazones. This one-pot, two-step protocol enables the insertion of various carbenes, including those previously unexplored in C-D skeletal editing chemistry, into indoles/pyrroles scaffolds to access 3-functionalized quinolines/pyridines. Mechanistic studies reveal a pathway involving the intermediacy of a 1,4-dihydroquinoline intermediate, which could undergo oxidative aromatization or defluorinative aromatization to form different carbon-atom insertion products.